Potensi isolat bakteri dari tailing pertambangan emas asal Kampung Warmanen Distrik Sausapor Kabupaten Tambrauw sebagai agen bioleaching tembaga (Cu) - Arvilein Maahury, Sevian; Massora, Maria; Mogea, Rina; Abubakar, Hermawati (Cassowary, 2026)
Gold mining in Village Warmanen, Sausapor District, Tambrauw Regency, has led to environmental pollution by heavy metals, one of which is copper (Cu), which has the potential to damage soil ecosystems and inhibit agricultural productivity. This research aims to isolate indigenous bacteria from former gold mining soil in Warmanen, test their ability to reduce Cu concentration through bioleaching technology, and identify the most promising bacterial isolates. The research method included soil sampling from the contaminated location, isolation and purification of bacteria. The bioleaching capability test was conducted by incubating eight bacterial isolates with copper-containing soil samples for 21 days on a laboratory scale. The decrease in Cu concentration in pellet fractions was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that the bioleaching process using indigenous bacteria was effective in reducing Cu concentration, especially in the solid (pellet) fraction of the soil. The accumulation of 3 bacterial isolates showed the highest potential on the 7th day, namely PW 1, PW 3, and PW 8, the isolate with the highest Cu accumulation was PW 1 with an accumulation of 0.30%